2011
DOI: 10.1007/s00128-011-0465-y
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of Chlorantraniliprole in Tomato Fruits and Soil

Abstract: The main objective of this study was to understand the residue and persistence behaviour of new insecticide chlorantraniliprole in tomato fruit and soil samples. Its residue was analyzed by HPLC and it dissipated in tomato fruit and soil following first order kinetics. The results showed half life (t(1/2)) value of 3.30 and 3.66 days for chlorantraniliprole in tomato fruit and soil, respectively. According to maximum residue limit (MRL) the pre-harvest interval (PHI) of chlorantraniliprole on tomato was 8-days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 6 publications
4
24
1
Order By: Relevance
“…five days for diazinon; four days for permethrin, and 13 days for chlorpyrifos) before distributing the crops into the markets. As the previous studies showed, considering preharvest period on the fruits and vegetables decreased the level of different pesticide residues (6,(19)(20)(21)(22)(23)(24)(25). As a general trend, the current study showed that the detected pesticides on tomato and cucumber were almost similar to those of some previous studies (26-28), but gradually higher than the results of the study by Abbassy (19).…”
Section: Discussionsupporting
confidence: 78%
“…five days for diazinon; four days for permethrin, and 13 days for chlorpyrifos) before distributing the crops into the markets. As the previous studies showed, considering preharvest period on the fruits and vegetables decreased the level of different pesticide residues (6,(19)(20)(21)(22)(23)(24)(25). As a general trend, the current study showed that the detected pesticides on tomato and cucumber were almost similar to those of some previous studies (26-28), but gradually higher than the results of the study by Abbassy (19).…”
Section: Discussionsupporting
confidence: 78%
“…Chlorantraniliprole, [3-bromo-N-[4-chloro-2-methyl-6-[(methyl amino) carbonyl] phenyl]-1-(3-chloro-2-pyridinyl)-1H-pyrazole-5-carboxamide], is a new anthranilic diamide pesticide developed by DuPont Crop Protection ( Fig 1 ) [ 22 ]. As described previously, it has a novel mode of action called ryanodine receptor activators which can lead to the depletion of intracellular calcium stores and cause impaired muscle regulation, paralysis and insect death [ 22 , 23 ]. The pesticide exhibits remarkable insecticidal efficacy and mammalian safety, and has been widely used for pest control in agriculture [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tomato, Solanum Lycopersicum L. (Solanaceae), is grown throughout the globe and its berry (fruit) constitutes an important part of human diet (Gupta et al, 2011). In Egypt, tomato is cultivated in about 221 thousand hectares which represent about 34 % of the average area of vegetables, while the fruits are basic component of the daily diet (Malhat et al, 2012a). Chemical pesticides are often applied for plant protection of the crop (Singh et al, 1980;1989;Awasthi, 1986).…”
Section: Introductionmentioning
confidence: 99%